Recent studies of human limbs rehabilitation using mechanomyography signal: a survey / M.D. Aliff-Imran … [et al.] - Daud, Muhamad Aliff Imran; Ahmad Puzi, Asmarani; Sidek, Shahrul Na’im; Abu Hassan, Salmah Anim; Zainuddin, Ahmad Anwar; Mohd Khairuddin, Ismail; Abd Mutalib, Mohd Azri (Faculty of Computer and Mathematical Sciences, 2023)
In rehabilitation and medical offices, mechanomyography (MMG) is a noninvasive, painless technology that can be applied for a number of goals. The goal of this study is to present a thorough overview of recent studies on mechanomyography-based human limb rehabilitation. The present study illu- minates the utilization of distinct transducers, including accelerometers, piezo e-lectric contact sensors, and condenser microphone sensors. Furthermore, it un- derscores the diverse results that these investigations have yielded. The main findings of this review, which apply to all of these forms of mechanomyogra- phy sensors, are that the ratio of sensor mass to muscle mass under observation is the most crucial factor in sensor selection. Therefore, it is believed that accel- aerometers are the most trustworthy devices for spotting MMG signals during both voluntary and induced muscular contraction.